Implementasi Multi Factor Evaluation Process Untuk Penentuan Lokasi TPA Di Kabupaten Lamandau Berbasis Web Aplication - Hidayat, Rahmat; Irmayanti, Ade; Tommy, Muhammad (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Determining the final waste disposal site is a complex problem for Lamandau Regency, which is a developing district, the more people there are every year, the more waste is produced. However, determining the location is still done subjectively without considering the influencing factors and is still manual. In problems like this, the decision support system can be used as a solution to help make decisions. This study aims to implement a decision support system in determining the final disposal site using the Multi-Factor Evaluation Process (MFEP) method which is applied in the form of a Web Application using a prototype model. In determining the final disposal site, there are 5 criteria to be assessed, namely: Cover Land with an initial weight of 0.2, Rain Intensity with an initial weight of 0.1, Nature Reserve with an initial weight of 0.2, Agriculture with an initial weight of 0.3 and Entrance roads with an initial weight of 0.2, and the number of alternatives consists of 5 locations. The findings show that the error rate of this system is below 5%. After testing all modules or system components, all of them were successful and feasible to be used as a tool in determining the final place of development.